2014
DOI: 10.1007/s10803-014-2166-y
|View full text |Cite
|
Sign up to set email alerts
|

Driving Behaviors in Adults with Autism Spectrum Disorders

Abstract: This pilot study investigated driving history and driving behaviors between adults diagnosed with autism spectrum disorders (ASD) as compared to non-ASD adult drivers. Seventy-eight licensed drivers with ASD and 94 non-ASD comparison participants completed the Driver Behavior Questionnaire. Drivers with ASD endorsed significantly lower ratings of their ability to drive, and higher numbers of traffic accidents and citations relative to non-ASD drivers. Drivers with ASD also endorsed significantly greater number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 43 publications
7
35
0
Order By: Relevance
“…Primary symptoms of ASD include deficits in social interaction, language and communication skills, and restricted, repetitive behaviors [2]. In addition to these core deficit areas, recent evidence suggests that adolescents and young adults with ASD have difficulty in learning safe driving skills [35]. In particular, compared with their typically developed peers, individuals with ASD demonstrated unsafe gaze patterns and higher levels of anxiety when operating a driving simulator [6], [7], responded slower during steering, identified fewer social hazards, and showed problematic multi-tasking ability [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Primary symptoms of ASD include deficits in social interaction, language and communication skills, and restricted, repetitive behaviors [2]. In addition to these core deficit areas, recent evidence suggests that adolescents and young adults with ASD have difficulty in learning safe driving skills [35]. In particular, compared with their typically developed peers, individuals with ASD demonstrated unsafe gaze patterns and higher levels of anxiety when operating a driving simulator [6], [7], responded slower during steering, identified fewer social hazards, and showed problematic multi-tasking ability [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The anecdotal experiences of these parents are supported by the extant literature, which suggests that ASD symptoms may compromise one’s ability to learn to drive and do so safely (Classen et al 2013; Cox et al 2016; Daly et al 2014; Reimer et al 2013; Chee et al 2017). However, the empirical evidence is limited regarding the nature and extent of the influence that these features have on driving skills.…”
Section: Introductionmentioning
confidence: 84%
“…This result is somewhat unexpected given that anxiety is a comorbid trait of autism. Anxiety has been theorised to potentially interfere with driving [7,8] and been used to explain a trend for heart rate increase with drivers on the autism spectrum in a simulated driving experiment [24]. With higher states of anxiety as well as findings of increased sensory sensitivities for individuals higher on the autism spectrum [26], it would have seemed likely that the participants on the autism spectrum would have found the warnings more annoying.…”
Section: Discussionmentioning
confidence: 99%
“…For example, surveys have shown that 63% of teenagers on the autism spectrum plan to obtain their driving license [14], even though their parents believe this is a challenging goal and one that the parents also believe that they might have substantial difficulty at performing safely [7]. A study by [8] used self-reports from a standardized driver behaviour questionnaire to examine differences between ASD and TD adults (mean age 33). Results showed that ASD drivers acquired licenses significantly later, drove significantly fewer days per week, and reported more traffic violations than non-ASD drivers.…”
Section: Introductionmentioning
confidence: 99%